Enhanced Recovery Care vs. Traditional Care in Laparoscopic Hepatectomy: A Systematic Review and Meta-Analysis - Zhou, Xueyin; Zhou, Xueyi; Cao, Jiasheng; Hu, Jiahao; Topatana, Win; Li, Shijie; Juengpanich, Sarun; Lu, Ziyi; Zhang, Bin; Feng, Xu; Shen, Jiliang; Chen, Mingyu (Frontiers in Surgery, 2022)
Background: Enhanced recovery care could alleviate surgical stress and accelerate recovery rates of patients. Previous studies showed the benefits of enhanced recovery after surgery program in liver surgery, but the exact role in laparoscopic hepatectomy is still unclear. Aim: We aimed to perform a meta-analysis to evaluate the safety and efficacy of enhanced recovery after surgery program in laparoscopic hepatectomy. Methods: The relative studies from a specific search of PUBMED, EMBASE, OVID, and Cochrane database from June 2008 to August 2018 were selected and included in this meta-analysis. The primary outcomes include length of hospital stay, duration to function recovery and overall postoperative complication rate. The secondary outcomes include operative time, intraoperative blood loss, cost of hospitalization, readmission rate, Grade I complication rate and Grade II-V complication rate. Results: 6 studies with 643 patients [enhanced recovery care (n=274) vs. traditional care (n=369)] were eligible for analysis. These comprised 3 randomized controlled trials and 3 retrospective studies. Enhanced recovery care group was associated with decreased hospital stay (SMD=-0.56, 95%CI=-0.83~-0.28, P<0.0001), shorter duration to function recovery (SMD=-1,14, 95%CI=-1.92~-0.37, P=0.004), and lower cost of hospitalization (MD=-1539.62, 95%CI=-1992.85~-1086.39, P<0.00001). Moreover, a lower overall postoperative complication rate was observed in enhanced recovery care group (RR=0.64, 95%CI=0.51~0.80, P<0.0001) as well as lower Grade II-V complication rate (RR=0.55, 95%CI=0.38~0.80, P=0.002), while there was no significant difference in intraoperative blood loss (MD=-65.75, 95%CI=-158.47~26.97, P=0.16), operative time (MD=-5.44, 95%CI=-43.46~32.58, P=0.78), intraoperative blood transfusion rate (OR=0.71, 95%CI=0.41~1.22, P=0.22), and Grade I complication rate (RR=0.73, 95%CI=0.53~1.03, P=0.07). Conclusion: Enhanced recovery care in laparoscopic hepatectomy should be recommended, because it is not only safe and effective, but also can accelerate the postoperative recovery and lighten the financial burden of patients.